2018
DOI: 10.3390/toxins10110480
|View full text |Cite
|
Sign up to set email alerts
|

A Time Series of Water Column Distributions and Sinking Particle Flux of Pseudo-Nitzschia and Domoic Acid in the Santa Barbara Basin, California

Abstract: Water column bulk Pseudo-nitzschia abundance and the dissolved and particulate domoic acid (DA) concentrations were measured in the Santa Barbara Basin (SBB), California from 2009–2013 and compared to bulk Pseudo-nitzschia cell abundance and DA concentrations and fluxes in sediment traps moored at 147 m and 509 m. Pseudo-nitzschia abundance throughout the study period was spatially and temporally heterogeneous (<200 cells L−1 to 3.8 × 106 cells L−1, avg. 2 × 105 ± 5 × 105 cells L−1) and did not correspond with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 90 publications
2
11
0
Order By: Relevance
“…The LOD for the two methods was 22 pmol L −1 (Trainer et al, 2009) and 32 pmol L −1 (Guannel et al, 2015) compared to an LOD of 10 pmol DA L −1 in our study. Most field studies quantified dDA using ELISA (Delegrange et al, 2018;Trainer et al, 2009;Trick et al, 2018) whereas LC-MS has only been used sporadically for quantification (Trainer et al, 2000;Umhau et al, 2018). The UPLC-MS/MS method developed here allowed fast quantification and a comprehensive spatial assessment of dDA.…”
Section: Quantification Of Dissolved Domoic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…The LOD for the two methods was 22 pmol L −1 (Trainer et al, 2009) and 32 pmol L −1 (Guannel et al, 2015) compared to an LOD of 10 pmol DA L −1 in our study. Most field studies quantified dDA using ELISA (Delegrange et al, 2018;Trainer et al, 2009;Trick et al, 2018) whereas LC-MS has only been used sporadically for quantification (Trainer et al, 2000;Umhau et al, 2018). The UPLC-MS/MS method developed here allowed fast quantification and a comprehensive spatial assessment of dDA.…”
Section: Quantification Of Dissolved Domoic Acidmentioning
confidence: 99%
“…Although particulate DA has been frequently measured in marine samples, only few studies covered dDA (Busse et al, 2006;Trainer et al, 2009;Umhau et al, 2018). Previous dDA quantification in seawater was based on a derivatisation procedure and subsequent quantification via HPLC and fluorescence detection (Pocklington et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Pseudonitzschia blooms were found to be associated with high DA levels in the eddy area of Juan de Fuca (Trainer et al, 2002, reviewed by Trainer et al, 2012. Umhau et al (2018) found a significant correlation between particulate DA and Pseudo-nitzschia abundance in an offshore area of Santa Barbara Basin, California (37 ± 124 pg DA cell -1 ). In the Bay of Seine, France, high DA concentrations were correlated with Pseudo-nitzschia australis, P. pungens and P. fraudulenta, but no correlation was found with a bloom of P. delicatissima (Thorel et al, 2017).…”
Section: Discussionmentioning
confidence: 85%
“…through enhanced stratification and nutrient (ammonium) input. Furthermore, possible influences of biotic factors including grazers (Leandro et al, 2010;Tammilehto et al, 2012;Selander et al, 2019), allelopathy (Van Meerssche et al, 2018) and bacteria (Lelong et al, 2012;Sison-Mangus et al, 2014) were not determined and therefore need to be addressed in future studies. pDA and Pseudo-nitzschia spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation